2023
DOI: 10.1088/0256-307x/40/9/096301
|View full text |Cite
|
Sign up to set email alerts
|

Phonon Focusing Effect in an Atomic Level Triangular Structure

Abstract: The rise of artificial microstructures has made it possible to modulate the propagation of various kinds of wave, such as light, sound and heat. Among them, the focusing effect is a modulation function of particular interest. In this work, an atomic level triangular structure is proposed to realize the phonon focusing effect in single-layer graphene. In the positive incident direction, our phonon wave packet simulation results confirm that multiple features related to the phonon focusing effect can be controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…With carbon fibers and the SiC matrix, the heat transfer relies mainly on phonon heat transfer, and the lattice vibrations are intensified with temperature, which results in an increase in thermal conductivity with temperature. [31] However, as the temperature increases, the presence of different defects in the SiC matrix leads to an increase in phonon scattering and a decrease in thermal conductivity. As a result, both the transverse and longitudinal thermal conductivities of the carbon fiber increase slowly with temperature, while the thermal conductivity of SiC matrix first increases when the temperature is not higher than 100 ∘ C, and then decreases with temperature.…”
Section: Tps Methods For Measuringmentioning
confidence: 99%
“…With carbon fibers and the SiC matrix, the heat transfer relies mainly on phonon heat transfer, and the lattice vibrations are intensified with temperature, which results in an increase in thermal conductivity with temperature. [31] However, as the temperature increases, the presence of different defects in the SiC matrix leads to an increase in phonon scattering and a decrease in thermal conductivity. As a result, both the transverse and longitudinal thermal conductivities of the carbon fiber increase slowly with temperature, while the thermal conductivity of SiC matrix first increases when the temperature is not higher than 100 ∘ C, and then decreases with temperature.…”
Section: Tps Methods For Measuringmentioning
confidence: 99%
“…For example, by phonon wave packet simulations, Hu et al demonstrated a remarkable effect of interfacial bonding strength on thermal transport across CNT-Si 20 and the polymer-solid, 21 figuring out that neither the diffuse mismatch model (DMM) nor the acoustic mismatch model (AMM) describes the interfacial scattering process quantitatively. In addition, based on this method, some interesting physical findings such as phonon interference 22–26 and phonon tunneling 27 have also been observed in interfacial thermal transport.…”
Section: Introductionmentioning
confidence: 98%
“…Initial theoretical models, i.e., acoustic mismatch model (AMM) [10] and diffusive mismatch model (DMM) [11,12] were proposed under the assumption of elastic scattering at interfaces. But these two models do not consider the realistic interfacial characteristics, prompting the development of more practical approaches like the atomic Green's function (AGF) [13][14][15][16] and wave-packet [17][18][19][20][21][22][23] method. However, these above-mentioned models solely account for elastic scattering processes, leading to significant deviations at high temperatures due to the increased contributions from inelastic scatterings.…”
Section: Introductionmentioning
confidence: 99%